Carbon stocks in compartments of soil organic matter 31 years after substitution of native Cerrado vegetation by agroecosystems - Ferreira, Eloisa Aparecida Belleza (2016)
Changes in carbon stocks in different compartments of soil organic matter of a clayey Latossolo Vermelho Distrófico (Typic Haplustox), caused by the substitution of native savanna vegetation (cerrado sensu stricto) by agroecosystems, were assessed after 31 years of cultivation. Under native vegetation, a stock of 164.5 Mg ha-1 C was estimated in the 0.00-1.00 m layer. After 31 years of cultivation, these changes in soil C stocks were detected to a depth of 0.60 m. In the case of substitution of cerrado sensu stricto by no-tillage soybean-corn rotation, a reduction of at least 11 % of the soil C pools was observed. However, the adoption of no-tillage as an alternative to tillage with a moldboard plow (conventional system) reduced CO2 emissions by up to 12 %.